Kekuatan Mengikat SKMHT Terhadap Pelaksanaan Eksekusi Karena Adanya Wanprestasi - Aslan Noor; Karin Veronica Wijaya; Ilva Yuniarsi Maruf; Muhammad Yusuf; Gregorius Patrich Setiawan (Syntax Idea)
Land is a security item for debt repayment that is most preferred by financial institutions that provide credit facilities, basically land is easy to sell, besides that the price for the land continues to increase and has a basis of rights which is the basis of proof of ownership of the land, and is difficult to engineer. So the Government created a program called Home Ownership Credit (KPR) which aims to make it easier for citizens to get a livable house. This research is a normative juridical research that is descriptive, which describes and analyzes systematically, factually, and accurately related to receivables in credit agreements that have been transferred. This research is a normative juridical research using a statutory approach and a case approach. The results of the author's research show that the power of SKMHT as the ownership of dependent rights made by Notaries does not meet the provisions stipulated in the UUJN, the legal consequence is that the power of proof becomes under hand. Thus, the creditor must make APHT and issue a Certificate of Liability so that the creditor gets his preferred rights in the Right to Dependent. But if it only makes SKMHT and does not make APHT, then to carry out execution parate, SKMHT has no binding legal force. As well as the application of the principle of good faith to the process of transferring receivables to third parties which is a solution to unlawful acts, namely that in this case if the creditor applies the principle of good faith and is committed in the agreement, then the sale of the object of the Right of Liability can be carried out under the lower hand if thus it will be able to obtain the highest price that benefits all parties and/or give priority to the debtor to be the buyer.